(untitled) (Bangladesh Journal of Botany, 2023)
Triticale is an important cool seasons cereal that can be used as human food and animal feed. In the present study relationship between physiological characteristics and grain yield in 18 triticale genotypes were determined. In terms of average grain yield were TBT16-11 (3597 kg/ha), Alperbey (3536 kg/ha) and Ayşehanım (3472 kg/ha) genotypes, respectively which were in the front row. According to the heatmap graph, it was determined that the traits were in two different clusters and that normalized difference vegetation index (NDVI), especially in the GS49 and GS60 stages, which gave a high correlation with the grain yield (GY). A strong similarity was seen between the Karma-Presto and Alperbey-TBT-16-11 triticale genotypes. Finally, it was determined that physiological properties are related to GY in triticale cultivation. Bangladesh J. Bot. 52(1): 187-196, 2023 (March)